Book review: Urban Geography. 30 years of the Simpósio Nacional de Geografia Urbana [National Symposium on Urban Geography]. Cities, revolutions and injustices: between private and public spaces, the right to the city and urban commons, by Ana Maria Leite de Barros, Cláudio Luiz Zanotelli e Vivian Albani (org.) - Zanotelli, Cláudio (Geografares, 2020)
The book was organized into seven parts, which correspond to the respective homonymous roundtables of the XVI SIMPURB held in Vitória between November 14 and 17, in 2019, a meeting that also marked the trajectory of 30 years of the first edition of Simpurb that took place in 1989 at USP and has been debating Brazilian urban geography every two years since then. The topics covered in the book are diverse and permeate urban geography and other types of knowledge that have the city and the urban as a space of knowledge.